Penerapan Konseling Individu dengan Teknik Cognitive Defusion dalam Mengatasi Overthinking - Ahmad Aldi; Komaruddin Komaruddin; Lena Marianti (Journal of Society Counseling, 2023)
The background of this research is that overthinking behavior makes clients always think about fears that may not necessarily happen, which results in feelings of trepidation in facing something that is considered dangerous for client A, UIN Raden Fatah Palembang student. So, it can be assumed about "Application of Individual Counseling with Cognitive Defusion Techniques in Overcoming overthinking (Case Study of Client "A" Student at UIN Raden Fatah Palembang)". This research aims: first, to find out the picture of overthinking experienced by client "A". Second, to find out the process and results of implementing individual counseling through cognitive defusion techniques in overcoming overthinking experienced by client "A". This research uses a descriptive qualitative approach. Robert K. Yin uses 3 data analysis techniques, including pattern matching, data explanation, and time series analysis. The results of the research show firstly, psychologically, they often feel excessively afraid and anxious, they are anxious about uncertainty, they worry about their future because they often feel afraid of failure, clients always don't focus on their activities when they are facing problems, and clients experience sleep disorders (insomnia). Physically: clients often feel tired, get sick easily, lack self-confidence, are often alone and easily irritated. Second, the application of individual counseling through cognitive defusion techniques to overcome the overthinking experienced by client "A", a student at UIN Raden Fatah Palembang, which was carried out over 4 meetings. The counselee began to realize and carry out the desired activities as a form of achievement. In this case, the counselee has made the goals he wants by drawing up a plan that the counselee wants to achieve after finishing college.